6-DOF wheeled parallel robot and its automatic type synthesis method. (March 2022) - Chu, Hongpeng; Qi, Bai; Qiu, Xuesong; Zhou, Yulin
Highlights: Wheels are introduced into parallel robots as kinematic pairs for the first time. The incidence matrix of a wheel is proposed to describe the wheel motion. An efficient automatic type synthesis method for wheeled parallel robots is presented. Two novel kinds of 6-DOF wheeled parallel robots were synthesized. A prototype of a 6-DOF wheeled parallel robot has been successfully developed. Abstract: Wheeled parallel robots combine the advantages of wheeled mobile robots and traditional parallel robots. In this paper, we have introduced wheels in parallel robots as kinematic pairs for the first time. Moreover, a new definition of the incidence matrix of the spatial branched chain is proposed and extended, and the incidence matrix of the wheel is given. Furthermore, we present an automatic type synthesis method for parallel robots with wheels. We synthesized 80 types of open-loop spatial chains with wheels. For the first time, we synthesized two kinds of wheeled parallel robots having six degrees of freedom (6-DOF) with new kinematic characteristics. In addition, a prototype of this 6-DOF wheeled parallel robot was successfully developed with a rated load up to 5 tons. These wheeled parallel robots can be widely used in the field of heavy equipment manufacturing, such as parts processing, transportation, orientation adjustment, automatic assembly, and other industrial operations.